Soil and climatic conditions as a main factor of draining meliorations in the Bahna Valley, Ukraine - Volodymyr Krool; Iryna Hodzinska (Kazimierz Wielki University, 2019)
The article studies the leading factors of influence on draining meliorations in theBahnaValley, such as soil cover and climatic conditions. The main types of soils are determined: Gleysols Umbric, Gleysols podzolic; Gleysols ferrum (rusty) podzolic; Podzoluvisols Stagnic; Phaeozems, slightly podzolic and sandy; Gleysols Umbric and Fluvisols Umbric and peat; Gleysols podzolic surface-bogged. It is established that the distribution of precipitation, which accounted for the warm season (70-80% of the annual norm), was a key factor among the climatic conditions in the region. It has been found that the valley may have a relative humidity of more than 90% within 100 days of a year and a relative humidity of 30% only within 20 days. The influence of Ukrainian Carpathians and adjoining flat territories results in specific conditions of humidification. It has been discovered that a great amount of precipitation (750-800 mm) and moderate annual temperatures contributed to the accumulation of excessive moisture that led to the boggy pedogenesis. The latter causes the formation of different swamped and boggy soils. The prevalence of the oversaturated soils in Bahna valley determined the need for drainage reclamation in the region.